Czego oczy nie widzą, tego archeologom żal – nowe metody dokumentacji sztuki naskalnej (RTI, DSTRETCH) - Wagner, Patrycja (Folia Praehistorica Posnaniensia, 2021)
This article presents the cognitive possibilities of the methods of documentation of rock art. It focuses on the latest and relatively recent documentation methods, such as RTI and DStretch. These techniques have been described in terms of the effectiveness of their application to various types of monuments, with particular emphasis on their application to the Franco-Cantabrian rock art. It was also emphasized that these techniques significantly affect the quality of the collected data and the analytical and interpretative level of cave art.